International human resource management: a global perspectives, practices and strategies for competitive success - Bhatia, S. K. (New Delhi : Deep Deep, 2005)
Business
Keywords: International HRM; HRM development; Globalization; Planning strategy; Global staffing; HRM practice; International transfer; Training and development; Global compensation; Global organization; Busness ethics; HRM practice-USA; Job flexibility; Performance management; Industrial relation; Labor unions; International trade